Efficacy and safety of pioglitazone added to alogliptin in Japanese patients with type 2 diabetes mellitus: a multicentre, randomized, double‐blind, parallel‐group, comparative study. Issue 12 (23rd October 2015) - Kaku, K.; Katou, M.; Igeta, M.; Ohira, T.; Sano, H.
Abstract : A phase IV, multicentre, randomized, double‐blind, parallel‐group, comparative study was conducted in Japanese subjects with type 2 diabetes mellitus (T2DM) who had inadequate glycaemic control, despite treatment with alogliptin in addition to diet and/or exercise therapy. Subjects with glycated haemoglobin (HbA1c) concentrations of 6.9–10.5% were randomized to receive 16 weeks' double‐blind treatment with pioglitazone 15 mg, 30 mg once daily or placebo added to alogliptin 25 mg once daily. The primary endpoint was the change in HbA1c from baseline at the end of treatment period (week 16). Both pioglitazone 15 and 30 mg combination therapy resulted in a significantly greater reduction in HbA1c than alogliptin monotherapy [−0.80 and −0.90% vs 0.00% (the least squares mean using analysis of covariance model); p < 0.0001, respectively]. The overall incidence rates of treatment‐emergent adverse events were similar among the treatment groups. Pioglitazone/alogliptin combination therapy was effective and generally well tolerated in Japanese subjects with T2DM and is considered to be useful in clinical settings.